Pengaruh Komunikasi Organisasi, Budaya Organisasi Dan Struktur Organisasi Terhadap Komitmen Organisasi (Studi Pada Pengurus PMII Rayon Al-Farabi 2022-2023) - Nor Sisah; Abdul Kodir Djaelani; M. Khoirul Anwarudin Broto Suharto (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to analyze the effect of organizational communication, organizational culture and organizational structure on organizational commitment. The research method used is descriptive quantitative. The population used in this research is PMII Rayon Al-Farabi 2022-2023 extra-campus organizational management. While the sample used in this study is probability sampling. There are 174 administrators and samples that can be processed are 64 administrators. The results of this study indicate that the variables of organizational communication, organizational culture and organizational structure simultaneously have a significant positive effect on organizational commitment. Keywords: Initiative Commitment, Organizational Communication, Organizational Culture and Transformational Leadership